2005
DOI: 10.1002/jnr.20436
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human neural stem cells for spinal cord injury in primates

Abstract: Recent studies have shown that delayed transplantation of neural stem/progenitor cells (NSPCs) into the injured spinal cord can promote functional recovery in adult rats. Preclinical studies using nonhuman primates, however, are necessary before NSPCs can be used in clinical trials to treat human patients with spinal cord injury (SCI). Cervical contusion SCIs were induced in 10 adult common marmosets using a stereotaxic device. Nine days after injury, in vitro-expanded human NSPCs were transplanted into the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
246
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(259 citation statements)
references
References 49 publications
9
246
0
4
Order By: Relevance
“…Previous studies have already shown that transplantation of human NSCs from fetal spinal cord or brain tissue improves locomotor functional recovery of SCI models [3,4]. Nevertheless, only recently has the efficacy of hiPS-NSC transplantation into SCI begun to be investigated [9].…”
Section: Transplantation Of Hips-lt-nes Cells Into the Injured Spinalmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have already shown that transplantation of human NSCs from fetal spinal cord or brain tissue improves locomotor functional recovery of SCI models [3,4]. Nevertheless, only recently has the efficacy of hiPS-NSC transplantation into SCI begun to be investigated [9].…”
Section: Transplantation Of Hips-lt-nes Cells Into the Injured Spinalmentioning
confidence: 99%
“…Transplantation into injured spinal cords of several different types of human NS/progenitor cells, derived from human fetal tissue [3,4] or from human embryonic stem cells (hESCs) [5,6], promotes functional recovery in animal models. Nonetheless, the mechanism underlying such functional improvement remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is very important to test proof of concept on the effectiveness of fetal NS/PCs transplantation for SCI in non-human primates. For this purpose, Iwanami et al [13,14] established a SCI model of a non-human primate, the common marmoset (Callithrix jacchus), and transplanted human aborted fetal forebrain-derived NS/PCs into this Figure 1 Microenvironment of the injured spinal cord. Because the immediately post-traumatic microenvironment of the spinal cord is in an acute inflammatory stage, it is not favorable for the survival and differentiation of NS/PC transplants.…”
Section: Regenerative Medicine For Sci Using Fetal-derived Ns/pcsmentioning
confidence: 99%
“…A number of studies have paid attention to the self-renewal capacity and multipotency of NS/PCs and tried to regenerate neural tissues lost as a result of neurodegenerative diseases and injuries. Particularly in the research field of spinal cord injury (SCI), mouse embryonic stem (ES) cell-derived NS/PCs [11] and rat embryonic spinal cord-derived NS/ PCs [12] have been transplanted into the injured spinal cord of rats, and human embryo-derived NS/PCs have been transplanted into the injured spinal cord of the common marmoset in preclinical studies, aiming at clinical application [13,14]. Safety of the cells and functional recovery were reported in all of the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%
“…We tested the efficacy of transplanting: 1) rat fetal spinal cord-derived neural stem/progenitor cells to treat rat SCI during the subacute stage after injury [12], 2) mouse fetal striatum-derived neural stem/progenitor cells to treat SCI in mice (an experiment that used luciferase luminescence to bioimage the transplanted cells) [13], and 3) human fetal brain-derived neural stem/progenitor cells to treat SCI in a nonhuman primate, the common marmoset (Callithrix jacchus), as part of a pre-clinical trial [14]. We found good functional recovery in all 3 cases and reported it ref [12][13][14]. These results led to strong expectations that human neural stem/progenitor cells that had been cultured and expanded in vitro would be applied to nerve regeneration in humans.…”
Section: Introductionmentioning
confidence: 99%